Two new design concepts for snake robot locomotion in unstructured environments - Liljebäck, Pål; Stavdahl, Øyvind; Pettersen, Kristin Y.; Gravdahl, Jan Tommy (Paladyn (Warsaw), 2010)
This communication presents and justifies ideas related to motion control of snake robots that are currently the subject of ongoing investigations by the authors. In particular, we highlight requirements for intelligent and efficient snake robot locomotion in unstructured environments, and subsequently we present two new design concepts for snake robots that comply with these requirements. The first design concept is an approach for sensing environment contact forces, which is based on measuring the joint constraint forces at the connection between the links of the snake robot. The second design concept involves allowing the cylindrical surface of each link of a snake robot to rotate by a motor inside the link in order to induce propulsive forces on the robot from its environments. The paper details the advantages of the proposed design concepts over previous snake robot designs.